SAT0603 Evaluating Quality of Care in Rheumatoid Arthritis: Patients Perspective. (15th July 2016) - Mahmood, S.; van Oosterhout, M.; de Jong, S.; Landewé, R.; van Riel, P.; van Tuyl, L.
Abstract : Background: Standardized measurement of outcomes allows for quality improvement of health care delivery. While a total of seven sets of RA quality indicators are available in the international literature, none of them reports extensively on the patients' representation (1). Objectives: As patients and healthcare providers have a different perspective regarding health care outcomes, we studied the patients' perspective on quality of care and incorporated this in the Dutch national Quality Registry for Rheumatoid Arthritis (DQRA). Methods: A group of patients (n=6) connected through the Dutch Arthritis Foundation, was consulted by focus group methodology and inquired about their positive and negative experiences and thoughts with rheumatology-care. During the meeting, all patients were required to form a "top-three" of most important domains; resulting domains were ranked in order of importance by the group. A set of nine domains (physician domains), defined by Dutch rheumatologists in a separate process were then introduced. These domains were compared with the domains as formed by the patients, resulting in the preliminary set of domains. The preliminary set of domains was sent to all RA members of the Dutch Arthritis Foundation panel (n=1132) through an online survey. Patients were asked to score all items on a seven-point Likert scale from "not important" to "extremely important", and to rank the items into a top five of important domains for the evaluation of quality of care. Results: The focus group discussion resulted in 7 domains: 1) education regarding the disease course; 2) attainability of healthcare providers; 3)availability of rheumatology nurses; 4) shared decision making; 5) insight in personal life of patient 6) insight in co-morbidities and co-medication 7) insight in limiting joints (for example after arthrodesis). The physician domains that were added to this set were; 8) adjustment of therapy based on disease activity; 9) prescription of a DMARD <3 months of diagnosis; 10) practicing according to a RA protocol and 11) registration time to first visit to rheumatologist. A total of 640 RA patients completed the online survey. Domains considered as "important or extremely important" for rheumatology care are displayed in figure 1 . The 5 domains that were ranked highest through the online survey included: 1) adjusting therapy based on the disease activity; 2) insight in personal life of patient; 3) shared decision making; 4) education regarding the disease course; 5) insight in co-morbidity and co-medication. Conclusions: This is the first study that has incorporated the patients' perspective on quality of RA care in the development of a national quality indicator set. Five domains were identified by patients, reflecting their perspective on quality of RA care. References: S. mahmood et al. 2015. Best Pract Res Clin Rheumatol Disclosure of Interest: None declared